TRANSLATION THEORIES AND THEIR APPLICATION IN ENGLISH-UZBEK LITERARY TRANSLATION - Xolmurzayev Oybek Shuxratovich (SAMARALI TA’LIM VA BARQAROR INNOVATSIYALAR JURNALI, 2026)
This article comprehensively analyses contemporary translation theories — those of Eugene Nida, Peter Newmark, Lawrence Venuti, and Gideon Toury — in the context of English-Uzbek literary translation. The paper examines in detail the categories of equivalence, adequacy, foreignization, and domestication, and identifies the characteristics of applying these theories in Uzbek translation practice. Drawing on examples from English literary texts and their Uzbek translations, the practical effectiveness of theoretical approaches is demonstrated. The findings justify the necessity of a balanced theoretical methodology in English-Uzbek literary translation and formulate practical recommendations for Uzbek translation studies.